PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS UNTUK ANAK-ANAK PADA GURU KKG BUNGO DANI - Diana Oktavia; Nur Habibah; Winda Trisnawati; Levandra Balti; Rahayu Sartika (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Implementing the Merdeka Curriculum in elementary school motivates this community service program. The implementation of this curriculum highlighted English teaching in Elementary school. Based on the initial need analysis study, it was found that the Elementary schools in Bungo Dani need training in teaching media development to support teaching English to young learners. This training involved 25 Elementary school teachers as the participants. Those participants were introduced and trained to prepare and develop the teaching media.